Induction of stable human FOXP3+ Tregs by a parasite‐derived TGF‐β mimic. Issue 8 (3rd June 2021) - Cook, Laura; Reid, Kyle T; Häkkinen, Elmeri; de Bie, Brett; Tanaka, Shigeru; Smyth, Danielle J; White, Madeleine PJ; Wong, May Q; Huang, Qing; Gillies, Jana K; Ziegler, Steven F.; Maizels, Rick M; et al.
Abstract: Immune homeostasis in the intestine is tightly controlled by FOXP3 + regulatory T cells (Tregs), defects of which are linked to the development of chronic conditions, such as inflammatory bowel disease (IBD). As a mechanism of immune evasion, several species of intestinal parasites boost Treg activity. The parasite Heligmosomoides polygyrus is known to secrete a molecule ( Hp‐ TGM) that mimics the ability of TGF‐β to induce FOXP3 expression in CD4 + T cells. The study aimed to investigate whether Hp‐ TGM could induce human FOXP3 + Tregs as a potential therapeutic approach for inflammatory diseases. CD4 + T cells from healthy volunteers were expanded in the presence of Hp‐ TGM or TGF‐β. Treg induction was measured by flow cytometric detection of FOXP3 and other Treg markers, such as CD25 and CTLA‐4. Epigenetic changes were detected using ChIP‐Seq and pyrosequencing of FOXP3 . Treg phenotype stability was assessed following inflammatory cytokine challenge and Treg function was evaluated by cellular co‐culture suppression assays and cytometric bead arrays for secreted cytokines. Hp‐ TGM efficiently induced FOXP3 expression (> 60%), in addition to CD25 and CTLA‐4, and caused epigenetic modification of the FOXP3 locus to a greater extent than TGF‐β. Hp‐ TGM‐induced Tregs had superior suppressive function compared with TGF‐β‐induced Tregs, and retained their phenotype following exposure to inflammatory cytokines. Furthermore, Hp ‐TGM induced a Treg‐like phenotype in in vivo differentiated Th1 and Th17 cells, indicating its potential to re‐program memory cells to enhance immune tolerance. These data indicate Hp‐ TGM has potential to be used to generate stable human FOXP3 + Tregs to treat IBD and other inflammatory diseases. Abstract : In this study, we showed a parasite‐derived TGF‐β mimic protein can induce stable FOXP3 + Tregs from both naive and pre‐committed human memory CD4 + T cells. This protein has potential for use as a novel immunoregulatory therapeutic for the treatment of inflammatory disease. ​